Search and seizure - Hasan, Nader R.; Lai, Mabel, 1984-; Schermbrucker, David, 1961-; Schwartz, Randy, 1971- (Criminal Law Series, 2021)
"The book, as part of our Criminal Law Series, is a very practical and balanced treatment of all issues related to search and seizure laws in Canada. Unlike drugs, sexual offences, fraud etc., which appeal to a particular sub-set within criminal law writ large, this book is one of general application, applying to all types of offences within the criminal justice system. The book focuses on issues related to the reasonable expectation of privacy, the search warrant application process, production orders, special Criminal Code search powers, ancillary orders, authorizations, warrantless searches, post-seizure reporting and detention and return of seized property, reviewing a search and seizure process, and the exclusion of evidence."--